Japanese students' reflections on high school preparation for university English classes : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education at Massey University, Manawatū, New Zealand - Knox, Daniel (Massey University, 2018)
High school English classes in Japan typically focus on passive writing skills at the expense of practical communication skills, leading many Japanese students of English to progress to university study in Japan lacking vital English conversational competence. The requirements at university differ in that students are required to speak and interact more, thus presenting difficulties in adjustment. The present study aimed to address this disparity by finding how students would like to be taught at high school to prepare them for the different environment they find in university English classes. A qualitative case study approach was used to gather data, including semi-structured interviews with seven English-major university students in Japan. The findings provide insights into students’ preferred language of instruction and perceptions on teaching at high school, initial difficulties in adjustment to university, greater enjoyment following adjustment to university, and perceptions on how students can aid their own transition. The findings from this study indicated that high school lessons were useful for the purpose of achieving in the university entrance test, but not useful for their broader studies at university. The students indicated they would have preferred more dynamic interaction in smaller classes, instead of the current large grammar-centered classes. It was also reported that Japanese high school teachers used little or no English in class and lacked knowledge of Western culture. The students would have preferred more classes with the Assistant Language Teacher (ALT) who, while not deemed immediately helpful for their university entrance exams, was considered helpful for students in making a successful transition to university.
Keywords: English language -- Study and teaching (Higher) -- Japanese speakers -- Interviews; English language -- Study and teaching (Higher) -- Japanese speakers -- Attitudes; English language -- Study and teaching (Secondary) -- Japan; English language -- Spoken English -- Japan